Congruent Leadership: values in action - Stanley, David (Blackwell Publishing, 2008)
To discuss the significance of an appropriate leadership theory in order to develop an understanding of clinical leadership. Leadership theories developed from management and related paradigms, particularly transformational leadership, may be ineffective in supporting nurses to gain insights into clinical leadership or to develop and implement clinical leadership skills. Instead, congruent leadership theory, based on a match between the clinical leaders' actions and their values and beliefs about care and nursing, may offer a more firm theoretical foundation on which clinical nurses can build an understanding of and capacity to implement clinical leadership or become clinical leaders.It is important to recognize that leadership theories based on a management paradigm may not be appropriate for all clinical applications. Education should be aimed specifically at clinical leaders, recognizing that clinical leaders are followed not for their vision or creativity (even if they demonstrate these), but because they translate their values and beliefs about care into action.